Metode Pentahelix Dalam Pengembangan Desa Wisata Ketapanrame - Nadira Aurelia Putri Setiawan; Tasya Maylina Ridwan; Nabila Aurellia Putri; M. Habib Nasrullah; Ahmad Anfirsto Fadi Sabilillah (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of Ketapanrame Tourism Village poses both challenges and opportunities that require comprehensive and sustainable strategies. This article analyzes the implementation of the Pentahelix Method in the context of developing this tourism village. The Local Government (Pemda) plays a crucial role in providing regulations, infrastructure, and financial support. Media serves as a primary tool for promoting the tourism village, with diversified efforts through print and digital media, as well as collaborations with the private sector. The Village Government (Pemdes) holds a strategic position in community empowerment and the development of tourism facilities. Associations, as representatives of the industrial sector, support village development through financial contributions and assistance. In conclusion, the development of Ketapanrame Tourism Village through the Pentahelix Method serves as an example of how cross-sector collaboration can create sustainable tourism growth and have a positive impact on the local community.